Relationship Between Rooming-In and Lactation Techniques with Breastfeeding Success in Azalea Ward, RSUD dr. M. Thomsen, Nias - Solidarisma Sarumaha; Masania Zebua; Marfuah Aceh; Paulina Hulu; Ikrar Suryanti Lase (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Successful breastfeeding is a key indicator of maternal and infant health during the postpartum period. Rooming-in and proper lactation techniques are two critical factors that contribute to breastfeeding success. However, various barriers, including maternal health conditions, limited institutional resources, and inadequate maternal knowledge, may hinder their implementation. This study aimed to examine the association between rooming-in practices and lactation techniques with breastfeeding success among postpartum mothers. A quantitative cross-sectional design was employed. The study population consisted of 38 postpartum mothers in the Azalea Ward of RSUD dr. M. Thomsen Nias, selected using a total sampling technique. Data were collected through observation checklists and structured questionnaires and analyzed using the Chi-square test. The 38 participants, 31 (81.6%) practiced rooming-in, 30 (78.9%) demonstrated proper lactation techniques, and 31 (81.6%) achieved successful breastfeeding. Statistically significant associations were found between rooming-in and breastfeeding success (p = 0.001), as well as between proper lactation techniques and breastfeeding success (p = 0.025). Rooming-in and proper lactation techniques are significantly associated with breastfeeding success among postpartum mothers. Hospitals should maintain rooming-in policies and provide structured, hands-on breastfeeding education programs to enhance maternal and infant health outcomes.